Cytogenetic Analysis of Two Species of Brachyhypopomus (Hypopomidae): New Inferences about Karyotypic Diversification of Grass Knifefish - Takagui, F. H.; Cardoso, A. L. [UNESP]; Dionisio, J. F.; Shibatta, O. A.; Giuliano-Caetano, L. (Pleiades Publishing, 2022)
Abstract: Among the bluntnose knifefish of the Hypopomidae family, Brachyhypopomus is the most specious genus, with 28 species widespread in hydrographic watersheds of South America. It is considered a monophyletic clade; however, some groups remain species complex and require taxonomic revision. In this study, Brachyhypopomus cf. draco and Brachyhypopomus gauderio were analyzed through cytogenetics to identify species-specific markers and propose evolutionary trends of the genus. Brachyhypopomus cf. draco had 2n = 26 (2m + 24a) and 18S terminal rDNA sites on pair 23. Brachyhypopomus gauderio exhibited a multiple sex chromosomes system, females had 2n = 42 (X1X1X2X2) and males had 2n = 41 (X1X2Y), both revealing a multiple nucleolus organizer regions system. The two species presented a similar heterochromatic pattern: pericentromeric, interstitial, and terminal blocks coincident with the nucleolus organizer regions. ChromEvol software evidenced 2n = 44 as a plesiomorphic characteristic of Brachyhypopomus. The karyotype evolution of this group is a dynamic process based on Robertsonian translocations, pericentric inversions, and intense reorganization of the heterochromatic elements.
Keywords: 18S rDNA; diploid number; Paranapanema River; Robertsonian translocations; sex chromosome; Tramandaí River